The Addition Effect of Parijoto (Medinilla speciosa) Puree for Postbiotic-Probiotic Yogurt and Extract for Nanoparticle Yogurt on the Physicochemical, Microbiological, Antibacterial, and Organoleptic Properties - Armeyliasari, Fara Brilian; Sinaga, Kresentia Verena; Noronha, Wihelmina Fransisca Pascoela; Dewi, Cecilia Shinta; Saleha, Rischa Amalia; Fardiaz, Dedi (Faculty of Animal Science Universitas Brawijaya, 2025)
Various forms, including puree and extract nanoparticles, affect the physicochemical, microbiological, and sensory properties of yogurt. Yogurt was produced from fresh cow’s milk fermented with Lactobacillus bulgaricus and Streptococcus thermophilus, with parijoto added at concentrations of 0%, 5%, 10%, 15%, and 20%. The studies were conducted using a Completely Randomized Design (CRD) with 4 replications. Parameters observed included pH, soluble protein, microstructure and mineral profile (postbiotic yogurt with puree); pH, Lactic Acid Bacteria (LAB) and antimicrobial (probiotic yogurt with puree); fat content, total acidity, and organoleptic properties (nanoparticle yogurt with extract). Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) or regression analysis when significant differences occurred. Results showed that postbiotic yogurt with puree significant affected (p < 0.05) the pH value (3.65-4.12); soluble protein (6.00-6.98 mg/mL) remained unaffected; FESEM-EDS analysis revealed a homogeneous microstructure with evenly distributed mineral elements; mineral mapping of carbon, oxygen, calcium, potassium, chlorine, magnesium, sodium and phosphorus. The result of probiotic yogurt with puree with the pH 3.53-3.58; LAB viability (8.11-9.41 log CFU/mL), while the highest LAB growth occurred at 10% parijoto concentration, whereas higher concentrations reduced bacterial viability due to phenolic compounds; fortified yogurt exhibited strong antibacterial activity against Escherichia coli and Salmonella typhi (11-20 mm inhibition zones). The result of nanoparticles yogurt with extract significantly reduced fat content (3.76-2.56%) and slightly decreased total acid (1.3315-1.2142%) with higher concentrations leading to lower sensory acceptance in taste, color, texture, and aroma. In conclusion, parijoto fruit fortification enhanced probiotic viability and antibacterial activity while influencing pH, fat, and sensory properties. Yogurt fortified with parijoto shows potential as a functional food with improved probiotic and antimicrobial characteristics, though optimization of concentration is needed to maintain desirable sensory quality.